TINGKAT KECEMASAN PADA WANITA USIA 48-55 TAHUN DALAM MENGHADAPI PERUBAHAN FISIK PADA MASA PRAMENOPAUSE DI PUSKESMAS HARAPAN RAYA PEKANBARU TAHUN 2016 - Oktaliza Elektrina (Jurnal Kesehatan Husada Gemilang, 2019)
Premenopause is a transition period between menopausal symptoms (about 40 years old) and menstrual cycle really leaves off (on the average of 51 years old). During the period, there will be significant physical changes. The purpose of this study was to describe the level of anxiety in women aged 48-55 in overcoming physical changes at Health Center of Harapan Raya Pekanbaru in 2016. This study is descriptive quantitative. The study was completed at Health Center of Harapan Raya Pekanbaru on May 10 to 20, 2016. The sample of the research was 77 respondents, which was completed through the accidental sampling technique and was analyzed over the univariate analysis. The results demonstrated that respondents with no anxiety was 0 (0%), mild was 41 (53.25%), moderate was 20 (25.97%) severe was 12 (15.59%) and very severe was 4 (5.20%). It thus can be decided that the anxiety level in women aged 48-55 in overcoming the physical changes at Health Center of Harapan Raya Pekanbaru was at mild category (41 respondents (53.25%)).